2002
DOI: 10.3748/wjg.v8.i3.464
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activities of human autologous cytokine-induced killer (CIK) cells against hepatocellular carcinoma cellsin vitroandin vivo

Abstract: Autologous CIK cells are of highly efficient cytotoxic effector cells against primary hepatocellular carcinoma cells and might serve as an alternative adoptive therapeutic strategy for HCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 27 publications
1
78
0
Order By: Relevance
“…CD3 + CD56 + cells are able to expand nearly 1 000-fold when they are cultured with a cytokine cocktail comprising interferon-γ (IFN-γ), interleukin-2 (IL-2), mAbs against CD3, and interleukin-1α (IL-1α), and have a characteristic which is more effective in the treatment of tumors with a non-major histocompatibility complex (MHC)-restricted mechanism, and a most effective project [6] . We have previously reported that CIK cells could suppress the growth of tumor cells in vitro when HCC cells were transplanted in mice [7][8][9][10] . Dendritic cells (DCs) are specialized antigen-presenting cells (APC) in the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…CD3 + CD56 + cells are able to expand nearly 1 000-fold when they are cultured with a cytokine cocktail comprising interferon-γ (IFN-γ), interleukin-2 (IL-2), mAbs against CD3, and interleukin-1α (IL-1α), and have a characteristic which is more effective in the treatment of tumors with a non-major histocompatibility complex (MHC)-restricted mechanism, and a most effective project [6] . We have previously reported that CIK cells could suppress the growth of tumor cells in vitro when HCC cells were transplanted in mice [7][8][9][10] . Dendritic cells (DCs) are specialized antigen-presenting cells (APC) in the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…A suitable method for evaluation of the immunoenhancing effects of immunotherapy has not been established yet. In humans, most of the cells obtained by cultivation of activated lymphocytes are reported to be cluster of differentiation (CD)-3 + T or NK cells [17], and the cytotoxic activity of these cells has been proved to increase after cultivation [40]. When canine lymphocytes were cultured with anti-CD3 antibody and human recombinant (hr) interleukin (IL)-2, the number of lymphocytes was observed to have increased [24].…”
mentioning
confidence: 99%
“…In 1991, Schmidt-Wolf et al (11) first reported that CIK cells possessed potential antitumor cell activity in the immunodeficient SCID mouse/human lymphoma model. Following this finding, additional studies indicated that CIK cells may be a better choice for patients with solid tumors and demonstrated that CIKs possess strong antitumor activity in vitro (24)(25)(26). A number of previous studies have also demonstrated that CIKs may reverse drug resistance in solid tumor cells (24)(25)(26).…”
Section: Discussionmentioning
confidence: 84%